Treatment of asymptomatic catecholaminergic polymorphic ventricular tachycardia. (May 2012) - Obeyesekere, Manoj N; Sy, Raymond W; Leong-Sit, Peter; Gula, Lorne J; Yee, Raymond; Skanes, Allan C; Klein, George J; Krahn, Andrew D
Catecholaminergic polymorphic ventricular tachycardia is a rare genetic disorder caused by mutations in genes involved in the intracellular calcium homeostasis of cardiac cells. Affected patients typically present with life-threatening ventricular arrhythmias precipitated by emotional/physical stress. The diagnosis is based on the demonstration of polymorphic or bidirectional ventricular tachycardia associated with adrenergic stress. Genetic testing can be confirmatory in some patients. Treatment for catecholaminergic polymorphic ventricular tachycardia includes medical and surgical efforts to suppress the effects of epinephrine at the myocardial level and/or modulation of calcium homeostasis. Mortality is high when untreated and sudden cardiac death may be the first manifestation of the disease. First-degree relatives of a proband should be offered genetic testing if the causal mutation is known. If the family mutation is not known, relatives should be clinically evaluated with provocative testing. In the absence of rigorous trials, prophylactic treatment of the asymptomatic catecholaminergic polymorphic ventricular tachycardia patient appears to reduce morbidity and mortality.